Sequence-targeted nucleosome sliding in vivo by a hybrid Chd1 chromatin remodeler - McKnight, Jeffrey N.; Tsukiyama, Toshio; Bowman, Gregory D. (Genome Research, 2016)
ATP-dependent chromatin remodelers regulate chromatin dynamics by modifying nucleosome positions and occupancy. DNA-dependent processes such as replication and transcription rely on chromatin to faithfully regulate DNA accessibility, yet how chromatin remodelers achieve well-defined nucleosome positioning in vivo is poorly understood. Here, we report a simple method for site-specifically altering nucleosome positions in live cells. By fusing the Chd1 remodeler to the DNA binding domain of the Saccharomyces cerevisiae Ume6 repressor, we have engineered a fusion remodeler that selectively positions nucleosomes on top of adjacent Ume6 binding motifs in a highly predictable and reproducible manner. Positioning of nucleosomes by the fusion remodeler recapitulates closed chromatin structure at Ume6-sensitive genes analogous to the endogenous Isw2 remodeler. Strikingly, highly precise positioning of single founder nucleosomes by either chimeric Chd1-Ume6 or endogenous Isw2 shifts phased chromatin arrays in cooperation with endogenous chromatin remodelers. Our results demonstrate feasibility of engineering precise nucleosome rearrangements through sequence-targeted chromatin remodeling and provide insight into targeted action and cooperation of endogenous chromatin remodelers in vivo.